2023
DOI: 10.3389/fimmu.2023.1186000
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-neutrophil interaction in COVID-19 and vaccine-induced thrombotic thrombocytopenia

Abstract: Coronavirus disease 2019 (COVID-19) is known to commonly induce a thrombotic diathesis, particularly in severely affected individuals. So far, this COVID-19-associated coagulopathy (CAC) has been partially explained by hyperactivated platelets as well as by the prothrombotic effects of neutrophil extracellular traps (NETs) released from neutrophils. However, precise insight into the bidirectional relationship between platelets and neutrophils in the pathophysiology of CAC still lags behind. Vaccine-induced thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 139 publications
(112 reference statements)
1
3
0
Order By: Relevance
“…Additional studies have found that calprotectin and NET levels are raised in vaccineinduced thrombocytopenia and thrombosis (VITT) after vaccination with ChAdOx1 nCoV-19 [23][24][25]. Moreover, recently, we reported increased DNase levels in the ChAdOx1 nCoV-19-vaccinated individuals, as measured via a novel DNase test, which correlated with their previously measured NET values [26].…”
Section: Introductionsupporting
confidence: 80%
“…Additional studies have found that calprotectin and NET levels are raised in vaccineinduced thrombocytopenia and thrombosis (VITT) after vaccination with ChAdOx1 nCoV-19 [23][24][25]. Moreover, recently, we reported increased DNase levels in the ChAdOx1 nCoV-19-vaccinated individuals, as measured via a novel DNase test, which correlated with their previously measured NET values [26].…”
Section: Introductionsupporting
confidence: 80%
“…The main characterized interactions occur via P-selectin-PSGL-1, CD40L-CD40, GPIb-Mac-1, and GPIIb-IIIa-SLC44A2 [ 96 ]. P selectin is the main platelet receptor for aggregation in COVID-19 [ 97 ]. Indirectly, both neutrophils and platelets form macrovesicles through membrane budding [ 98 ] and secrete inflammatory mediators such as cytokines and IL-6 [ 99 , 100 ].…”
Section: Implications Of Altered Molecular Processes In Long Covid Sy...mentioning
confidence: 99%
“…Additionally, a hypofibrinolytic phenotype and increased thrombin generation are described, leading to a hypercoagulable state [ 111 ]. A distinct platelet-neutrophil interaction that mimics an acute infection is seen in long COVID patients [ 97 ]. Increased D-dimer and interleukin-6 levels are also observed in long COVID patients and might be indicative of microvascular thrombosis [ 112 , 113 ].…”
Section: Implications Of Altered Molecular Processes In Long Covid Sy...mentioning
confidence: 99%
“…Platelets can be activated by various stimuli such as immune complexes [16], viruses (e.g., SARS-CoV-2) [73], and vascular injury [74] resulting in either a direct or indirect activation of neutrophils. With the former, activated platelets can bind and activate neutrophils via various corresponding receptors such as P-selectin/PSGL1, GP1bα/Mac-1, αIIβ3/Mac-1, ICAM-2/Mac-1, CD40L/CD40, and GPIIb/IIIa/SLC44A2 [75,76] although P-selectin/PSGL1 has been the most prominent interaction found to be involved in direct platelet-induced NETosis [15,18] (Figure 1). Crosstalk between platelets and neutrophils enhance the thrombotic process as neutrophils become activated and consequently undergo NETosis [15], while NETs in turn can promote platelet activation [77][78][79], further perpetuating the thrombotic condition.…”
Section: Mechanisms Of Neutrophil Activationmentioning
confidence: 99%